2021
DOI: 10.1371/journal.pone.0256322
|View full text |Cite
|
Sign up to set email alerts
|

Modelling speed behaviour in rural highways: Safety analysis of driving under adverse road-weather conditions

Abstract: This study proposes a methodical approach to model desired speed distributions under different road-weather and traffic conditions followed by identification of road-weather conditions with potentially higher safety risks in rural divided highways located in extremely cold regions. Desired speed distributions encompassing unique combinations of adverse road-weather and traffic conditions are modelled as normal distributions characterized by their means and standard deviations formulated based on two principal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(27 citation statements)
references
References 23 publications
2
25
0
Order By: Relevance
“…In this study, speed distributions are modelled based on two assumptions: (i) observed speeds reasonably represent drivers’ desired speeds, and (ii) the population of individual desired speeds under a specific combination of speed-decisive factors can be modelled as a normal distribution characterized by a mean of μ and an SD of σ . Study data used in this investigation supports both assumptions ( 5 ). In fact, it is well documented that desired speed distributions can be modelled as normal distributions under most conditions ( 5 , 23 ).…”
Section: Methodssupporting
confidence: 80%
See 4 more Smart Citations
“…In this study, speed distributions are modelled based on two assumptions: (i) observed speeds reasonably represent drivers’ desired speeds, and (ii) the population of individual desired speeds under a specific combination of speed-decisive factors can be modelled as a normal distribution characterized by a mean of μ and an SD of σ . Study data used in this investigation supports both assumptions ( 5 ). In fact, it is well documented that desired speed distributions can be modelled as normal distributions under most conditions ( 5 , 23 ).…”
Section: Methodssupporting
confidence: 80%
“…Study data used in this investigation supports both assumptions ( 5 ). In fact, it is well documented that desired speed distributions can be modelled as normal distributions under most conditions ( 5 , 23 ). Yet, we hypothesize that drivers’ speed choice is dependent on the prevailing driving conditions; thus, the speed distribution parameters are expected to vary under different combinations of speed-decisive factors.…”
Section: Methodssupporting
confidence: 80%
See 3 more Smart Citations